El Recreo, public tribune Women pioneers in education and journalism in the XIX century - Ortiz Fernández, Carolina (2018)
This article explores the women ’s proposal in the magazine El recreo, founded and directed by Clorinda Matto de Turner in 1876. In the first part, an overview of the very first publications during the early years of the Republic is developed. Following to the next part are the main features of Matto de Turner’s journalistic career, and in the third one, the purpose of the publication is explored. It is demonstrated that Clo- rinda Matto de Turner, Trinidad Enriquez, Mercedes Cabello took the reins of the public spaces of communication and knowledge, to propi- tiate and defend women’s education and an independent journalism, and they were facing furious attacks of power groups that feared losing their privileges.